Binder-free hydrogen storage composite Co9S8/rGO: A prospective anode for flexible energy storage device with high energy density. (10th September 2020) - Wang, Na; Hou, Wenjing; Chang, Yunzhen; Song, Hua; Li, Honggang; Li, Yanping; Han, Gaoyi
Highlights: The hydrogen storage materials used as the anode of the energy storage device. The electroless plating method was used to prepare flexible Co coating/carbon cloth. The Co9 S8 -based electrode is got by hydrothermally treating Co coating. Assembled asymmetric cells exhibit high energy density and capacity. Abstract: Flexible energy storage devices attracted extensive attention due to their application in personal wearable electronic products. However, the applications of flexible energy storage devices, especially supercapacitors are limited by their low energy density, because anode materials with large capacitance are scarce for the devices based on aqueous electrolyte. Therefore, developing high-performance anode is an effective way to break through the low energy density of flexible devices. Herein, the electroless plating method was used to prepare a flexible cobalt metal substrate based on carbon cloth (CC). The composite of Co9 S8 and reduced oxide graphene (rGO/Co9 S8 (rGO)/CC) is prepared by one-step hydrothermal method as a flexible anode with outstanding performance. Benefiting from the high hydrogen storage capacity of rGO/Co9 S8 (rGO), only a small amount of anode materials are needed to match the capacity of the cathode material of rGO/Ni3 S2 (rGO). The optimized flexible device assembled by using rGO/Co9 S8 (rGO) as negative electrode and rGO/Ni3 S2 (rGO) as positive electrode shows a high specific capacitance of 192.4 mAh g −1 at the current density of 4.0 A g −1, large energy density (168.1 Wh kg −1 at 3.5 kW kg −1 ). Furthermore, the network structure of the electrode can provide enough space for the expansion and contraction of the electrode materials during the repeated charging and discharging process, so the device exhibits good cycle stability (the capacitance of the device can retain 84.3% after 6000 cycles). Moreover, the device also exhibits remarkable flexibility. These results reveal that this kind of electrochemical hydrogen storage material can be developed as a promising anode in flexible energy storage devices.